Pengaruh Faktor Eksternal dan Berbagai Keputusan Keuangan terhadap Nilai Perusahaan - Darminto Darminto (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Purpose of this research to explains level of significant influence exogenous variable external factor, real asset investment decision, financing decision, asset management decision, financial performance and dividend policy to corporate value. The seven variable kinds of forms twelve the causal relation is having ladder so that there are twelve hypotheses tested. Approach model from this research follows philosophic of mainstream or paradigm positivist. Population of research 133 corporate and samples is determined by using method proportionate stratified random sampling in obtaining 112 corporate or 84, 21 % from population and analysis unit 896 financial statement. Data analyzer capable to explain the causal relation, which is complex and having laddered that, is Structural Equation Modeling. Hypothesis test out of twelve (12) hypotheses, which in rising, result of his its eleven (11) hypotheses received, because in supporting empiric data meaning significant that is H1 up to H11 There are one (1) hypothesis refused, because not in supporting meaning empiric data significant not to that is H12 Alteration of external factor followed by real asset investment had an influential on significant to asset management of later on influences financial performance. Financing decision and asset management influences financial performance. Financing decision and financial performance reached need to be considered in taking dividend policy. Financial decision and financial performance had an influential on significant to corporate value.